2023
DOI: 10.3390/nu15040874
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein Intake Early in Life on Kidney Volume and Blood Pressure at 11 Years of Age

Abstract: High protein intake has been associated with kidney hypertrophy, which is usually reversible; however, when it occurs early in life, it could lead to cell programming with a long-lasting effect. This study aimed to assess whether higher protein ingestion early in life has a persistent effect on kidney volume at 11 years of age, as well as its influence on blood pressure. This is a secondary analysis of a randomized control trial that compared the growth of infants fed with a higher-protein formula versus those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Moreover, because a higher maximum creatinine between day 3 and day 7 after birth was a risk factor for systolic HBP in our cohort, the role of kidneys is likely, as suggested by this study performed in general population where early high protein intake was associated with later systolic hypertension and an increase in kidney volume at 11 years of age. 4 The mechanism underlying this relationship could be the role of senescence pathways as observed in rats. 36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, because a higher maximum creatinine between day 3 and day 7 after birth was a risk factor for systolic HBP in our cohort, the role of kidneys is likely, as suggested by this study performed in general population where early high protein intake was associated with later systolic hypertension and an increase in kidney volume at 11 years of age. 4 The mechanism underlying this relationship could be the role of senescence pathways as observed in rats. 36 …”
Section: Discussionmentioning
confidence: 99%
“…This association could be mediated by altered kidney function. 4 Literature suggests postnatal nutritional intakes could be determinants of later HBP at 6.5 years of age in infants born very preterm as well. 5 Concerns have been raised that not only low intakes but also high intakes in infancy might contribute to higher blood pressure (BP) and increased cardiovascular risk later in life in this high‐risk population.…”
mentioning
confidence: 99%
“…Moreover, because a higher maximum creatinine between day 3 and day 7 after birth was a risk factor for systolic HBP in our cohort, the role of kidneys is likely, as suggested by this study performed in general population where early high protein intake was associated with later systolic hypertension and an increase in kidney volume at 11 years of age. 4 The mechanism underlying this relationship could be the role of senescence pathways as observed in rats. 36 Overall, in this study we observed 2 risk factors for later systolic BPH at 5 years: maximal creatinine between days 3 and 7, a marker for vulnerable kidney, and exposure to high amino acid intake.…”
Section: Discussionmentioning
confidence: 99%
“…The mean (SD) systolic BP was higher in the exposed group: 101. 4 S5A), but not with diastolic HBP (aOR, 1.00 [95% CI, 0.54-1.85] and aOR, 0.87 [95% CI, 0.51-1.48]). Moreover, the linear relationships between amino acid intake at day 7 after birth or maximal plasma creatinine between day 3 and day 7, and systolic BP (adjusted β=1.61 mm Hg 1 g/kg of amino acid intake [95% CI, 0.28-2.93] and adjusted β=1.94 mm Hg per 50 μmol of creatinine [95% CI, 0.31-3.57], respectively) were significant (Figure S5B).…”
Section: Sensitivity Analysesmentioning
confidence: 98%